Environmental aspects of craft technologies of health products from the position of the sustainable development concept - Stetsenko, Natalia (My University, 2025)
Craft production of healthy food products is a relevant trend in the modern market, it is focused on creating high-quality products with unique organoleptic properties, high quality and safety indicators, as well as a positive impact on consumer health. The philosophy of craft production is based on the principles of sustainable development and responsible consumption. Manufacturers strive to create a product that not only meets the needs of consumers, but also takes into account the interests of future generations. This is manifested in all aspects of production: from the selection of raw materials, defining the concept of a new health product and choosing its packaging. The development of craft production of health products directly contributes to the implementation of key sustainable development goals, namely Goal 2 - Eradicate hunger, ensure food security and improved nutrition, as well as promote sustainable agriculture; Goal 3 - Ensure healthy lifestyles and well-being for people of all ages; and Goal 12 - Ensure the transition to sustainable consumption and production patterns. Крафтове виробництво продуктів здорового харчування є актуальним трендом на сучасному ринку, воно орієнтоване на створення високоякісної продукції з унікальними органолептичними властивостями, високими показниками якості та безпеки, а також позитивним впливом на здоров'я споживачів. Філософія крафтового виробництва базується на принципах сталого розвитку та відповідального споживання. Виробники прагнуть створити продукт, який не лише відповідає потребам споживачів, а й враховує інтереси майбутніх поколінь. Це проявляється в усіх аспектах виробництва: від вибору сировини, визначення концепції нового продукту для здоров'я та вибору його упаковки. Розвиток крафтового виробництва продуктів для здоров'я безпосередньо сприяє реалізації ключових цілей сталого розвитку, а саме Цілі 2 – Викорінення голоду, забезпечення продовольчої безпеки та покращення харчування, а також сприяння сталому сільському господарству; Цілі 3 – Забезпечення здорового способу життя та благополуччя людей різного віку; та Цілі 12 – Забезпечення переходу до сталих моделей споживання та виробництва.
Keywords: craft technologies; health food; sustainable development; sustainable development goals; крафтові технології; сталий розвиток; цілі сталого розвитку; кафедра технології оздоровчих продуктів